Analisis Kemampuan Berpikir Kritis dalam Menyelesaikan Problem Based Tasks Berdasarkan Perbedaan Gender - Uzer Al Khafid; Irwani Zawawi; Sri Suryanti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study used descriptive research with a qualitative research approach. This research was conducted at SMP Negeri 29 Gresik. The subjects in this study are class VII A, research subjects are selected based on the criteria that have been set in the results of the critical thinking ability test in solving problem-based tasks 1. From each criterion, 2 students (1 female student and 1 male student) were selected who got the highest score. Based on the results of the mathematical critical thinking ability test, 2 students were selected as research subjects for the next interview process. Based on the results of the study, it can be concluded that in the subject of gender differences, each subject, both male and female gender, has their own advantages and disadvantages in solving existing problems, not significantly showing that there are differences in critical thinking skills between male and female subjects, this can be seen from the results of the PBT II test and interviews where the high categories of LK and Pr subjects are equally able to answer each questions related to indicators and also seen from the score results obtained that LK and Pr subjects on each indicator have the same number of high scores, namely on indicators of interpretation, analysis, evaluation and inference.